Orang Muda Katolik: Jembatan Kasih Di Tengah Keragaman - Anselmus D. Atasoge (STIPAS St. Sirilus Ruteng, 2018)
Indonesia is a multicultural nation based on ethnic, religious and cultural. Keeping this multiculturalism a call for all people, including Young Catholics. In that context, it is true what the Catholic youth proclamated in the Asian Youth Day 7, 2017 in Yogyakarta. In this moment they promise to turn a violent world into a world of peace and a life of safety in diversity. Asian youth promise not to repeat the history of violence whether labeled religion, ethnicity or other labelitas. The promise is revealed in their endeavors to live the joy of the gospel in the diversity. This paper gives meaning to the necessity of viewing multiculturalism as a part of civilized life. My focus, I want to give socio-theological perspective as baseline notes as a framework for young Catholics in the struggle to live the joy of the gospel in the world diversity.